Innovative alternative of wineries wastewater treatment: mathematical modeling (2013)
A secondary alternative treatment for the wastewater depuration of the winery industry was evaluated. In order to determine their efficiency, oxygen chemical demands was chosen as reference parameter. The experimental work was performed in a tubular reactor consisting of a fixed bed of gravel, which analyzed the influence of using different particle sizes and flow of effluent to be treated. A decrease of oxygen chemical demands value was observed (between the 16 and 54%). Better decrease percentages of this parameter were obtained working with smaller effluents flows to try and with a bed constituted by smaller particles too. A mathematical model was developed, analyzing different kinetic of the purification process according to the experimental obtained values. As a result of this analysis, a good approach of the experimental values was obtained using a kinetics order equal to six.